IMPLEMENTASI MEDIA KOMIK BERBASIS KEARIFAN LOKAL MALANG DENGAN PENDEKATAN CRT UNTUK MENINGKATKAN KEMAMPUAN MEMAHAMI ISI BACAAN - Khasanah, Kholitdatul; Yuniawatika; Lilyana Abiba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low ability of students to understand reading content due to a lack of variety in learning media and approaches. The purpose of this study was to improve reading comprehension skills through the use of comic media based on local wisdom in Malang with a Culturally Responsive Teaching (CRT) approach in Indonesian language lessons for fourth-grade elementary school students. This study used the Classroom Action Research (CAR) method conducted in two cycles. Each cycle consisted of planning, implementation of actions, observation, and reflection. The results of the study showed an increase in the percentage of student learning achievement from 33.33% in the pre-cycle to 62.96% in cycle I, and further increased to 88.89% in cycle II. The implementation of locally-based comic media using the CRT approach has proven effective in enhancing students' ability to comprehend reading content and fostering meaningful connections between students and the contextualized material being studied.